Effects of Corn Dried Distillers Grains with Solubles Withdrawal on Finishing Pig Performance - A. B. Lerner; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; M. W. Allerson (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 860 finishing pigs [C48 or L42 × 327; initially 146 ± 11.1 lb body weight (BW)] were used in a 76-d experiment to evaluate the effects of removing corn dried distillers grains with solubles (DDGS) from diets at varying intervals before harvest. Pigs were fed diets containing 40% DDGS until the start of the trial. Diets contained 35% DDGS from approximately 146 to 180 lb and 30% until the completion of the trial. Pen served as the experimental unit, and there were 7 replicate pens per treatment with 23 to 25 pigs per pen. Pens were blocked by BW within the barn and allotted to 1 of 5 dietary treatments differentiated by the number of days before slaughter that diets containing DDGS were withdrawn and replaced with corn-soybean meal-based diets. Withdrawal times consisted of the following: 76 (no DDGS fed), 42, 27, 15, or 0 d (no withdrawal) before the time all pigs were marketed. At the time of harvest, all pigs were sent to a commercial processing facility for carcass data collection. For the overall period from d -76 to 0, as time of DDGS withdrawal increased, average daily gain (ADG) and final BW also increased (linear,P<0.018), while feed:gain ratio (F/G) improved (quadratic,P= 0.022). Average daily feed intake (ADFI) quadratically decreased (P= 0.030) with increasing withdrawal time. There was a linear increase (P= 0.009) in hot carcass weight (HCW), with a marginally significant increase in carcass yield (linear,P= 0.094) with increasing DDGS withdrawal time. Loin depth and lean percentage did not demonstrate any evidence for treatment differences (P>0.132). Backfat was linearly increased (P= 0.030) with a marginally significant (P= 0.084) quadratic response with increasing DDGS withdrawal time. Lastly, the iodine value of belly fat was increased (linear,P<0.034) with increased feeding duration of DDGS. Feed cost per pig and income over feed cost (IOFC) per all pigs that started on the experiment were increased (linear,P<0.048) with increasing withdrawal time. Feed cost per lb of gain did not demonstrate evidence for treatment differences (P>0.505). When based on the number of pigs marketed at the end of the experiment, feed cost per pig was increased (linear,P= 0.001) with increasing withdrawal time, though feed cost per lb of gain and IOFC did not have evidence for differences (P>0.186). Carcass gain value was increased (linear,P= 0.001) with increased DDGS withdrawal time. In conclusion, removing pigs from DDGS for longer periods before slaughter increased ADG and improved F/G, resulting in increased HCW. Belly fat iodine value was inversely related to the length of DDGS withdrawal, with the highest iodine value (IV) resulting from pigs that consumed DDGS for the entire finishing period. The advantages in final BW and HCW seen in the present data may encourage producers to remove DDGS from finishing diets earlier than commonly practiced.
Keywords: dried distillers grains with solubles; DDGS; finishing pigs; withdrawal